Russia-Ukraine Conflict and its Implications for Global Food Insecurity and Immigrant Influx - Asif, Ramsha; Khalid, Iram (Annals of Human and Social Sciences, 2024)
The Russia-Ukraine conflict has unleashed a profound humanitarian crisis, resonating globally through its impact on food security and precipitating a surge in immigration. The conflict-induced migration has led to a significant influx of immigrants, both internally and across borders, presenting myriad challenges. Therefore, this paper explores the intricate dynamics of how the conflict disrupts food production, distribution, and access, delving into the direct effects on millions in the region. This article is a qualitative research study that uses exploratory and explanatory research approaches to explore subtle recommendations, revealing the astounding interplay of factors escalating food insecurity. This paper reveals the need for sustained international efforts and organized responses that address both the immediate needs and the long-term implications are crucial. The food security and immigration influx challenges demand innovative solutions and a holistic and adaptive approach for recovery, resilience, and stability in the face of the Russia-Ukraine conflicts.